Ideological, social and cultural aspects of events - Moufakkir, Omar,; Pernecky, Tomas, (CABI, 2014)
This book addresses the social and cultural side of events and explores the role they have in fostering change and community development. It examines the transformatory function of events in the context of development studies - as phenomena that can promote and facilitate human development, including social, societal and individual change. The book is organized into five thematic parts. The first part (chapters 1-2) seeks to establish that events are first and foremost a societal phenomenon - a fact that is often overlooked in the event management literature. The second part (chapters 3-5) focuses specifically on the ways in which ideologies underpin events. The third part (chapters 6-8) deals with the construction of values and collective visions for events. The fourth part (chapters 9-14), under the heading of Multiculturalism, Community and Integration, brings together a collection of case studies that are connected by a broader focus on the importance of events for communities. The last section (chapter 15) presents an overall summary and conclusions.